2015
DOI: 10.1002/pola.28010
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl phenylboronic acid controlling co‐monomer for nitroxide mediated synthesis of thermoresponsive poly(2‐N morpholinoethyl methacrylate)

Abstract: Low concentrations of 4-vinylphenylboronic acid (VPBA) were copolymerized with 2-N-morpholinoethyl methacrylate (MEMA) by nitroxide mediated polymerization using BlocBuilder TM unimolecular initiator at 80 to 90 8C. The MEMA/VPBA copolymerizations were performed at initial feed compositions (f VPBA,0 ) of 0.05 to 0.10 VPBA, with f VPBA,0 5 0.10 using dimethylacetamide (DMAc) solvent being most effective, as seen by a linear increase in number average molecular weight, M n , versus conversion and low dispersity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…We also used 4‐vinylphenylboronic acid (VPBA), which can be applied towards glucose sensing in combination with a thermoresponsive DMAEMA co‐monomer. [ 144 ] One particular interesting aspect concerning VBK was the very low concentration required for it to be an effective controlling co‐monomer ~1 mol%, [ 145 ] compared to ~8 mol% for styrene, and using a combination of kinetic studies and ESR studies revealed the subtle role of the reactivity ratios in increasing the probability of a terminal VBK monomer unit attached to the nitroxide. [ 146 ] Other controlling co‐monomers like 2‐vinylpyridine were successfully implemented to provide added pH‐responsiveness and tuning to the resulting copolymer LCST.…”
Section: The 2010smentioning
confidence: 99%
“…We also used 4‐vinylphenylboronic acid (VPBA), which can be applied towards glucose sensing in combination with a thermoresponsive DMAEMA co‐monomer. [ 144 ] One particular interesting aspect concerning VBK was the very low concentration required for it to be an effective controlling co‐monomer ~1 mol%, [ 145 ] compared to ~8 mol% for styrene, and using a combination of kinetic studies and ESR studies revealed the subtle role of the reactivity ratios in increasing the probability of a terminal VBK monomer unit attached to the nitroxide. [ 146 ] Other controlling co‐monomers like 2‐vinylpyridine were successfully implemented to provide added pH‐responsiveness and tuning to the resulting copolymer LCST.…”
Section: The 2010smentioning
confidence: 99%
“…Condensation reaction is a chemical reaction in which multiple reactants produce a desired product with accompanying formation of small molecules . In a recent study, boronate ester formation was used to synthesis lignin graft copolymers [Scheme (e)] . The copolymers were prepared by covalent linkage between aryl boronic acid end functionalized PCL and organosolv lignin in the presence of 1,2‐dichloroethane for 17 h at 65 °C.…”
Section: Graft‐ontomentioning
confidence: 99%
“…Traditionally, NMP was restricted to the polymerization of styrenic monomers using 2,2,6,6‐tetramethyl‐piperidine 1‐oxyl initiator (TEMPO) . NMP's recent development has been accelerated by the development of initiators based on alkoxyamines such as N ‐tert‐butyl‐ N ‐[1‐diethylphosphono‐(2,2‐dimethylpropyl)]nitroxide (SG1) and 2,2,5‐trimethyl‐4‐phenyl‐3‐azahexane‐3‐nitroxide (TIPNO), which have allowed the controlled polymerization of a wider range of monomers including acrylates, acrylamides, and methacrylates (with a small addition of “controlling” comonomers) . NMP controls the radical concentration for a significant period of the polymerization, thereby minimizing irreversible termination reactions.…”
Section: Introductionmentioning
confidence: 99%
“…8 NMP's recent development has been accelerated by the development of initiators based on alkoxyamines such as N-tert-butyl-N-[1-diethylphosphono-(2,2-dimethylpropyl)]nitroxide (SG1) 9 and 2,2,5-trimethyl-4-phenyl-3-azahexane-3nitroxide (TIPNO), 10 which have allowed the controlled polymerization of a wider range of monomers including acrylates, [11][12][13][14] acrylamides, [15][16][17] and methacrylates (with a small addition of "controlling" comonomers). [18][19][20][21][22][23] NMP controls the radical concentration for a significant period of the polymerization, thereby minimizing irreversible termination reactions. Consequently, chain end fidelity and narrow molecular weight distributions are the result, which superficially resemble the features of truly living polymerizations.…”
mentioning
confidence: 99%